The transcriptome landscapes of allantochorion and vitelline-chorion in equine day 30 conceptus - Shen, Yingchao; Ren, Hong; Davshilt, Toli; Tian, Shuyue; Wang, Xisheng; Yi, Minna; Ulaangerel, Tseweendolmaa; Li, Bei; Dugarjav, Manglai; Bou, Gerelchimeg (Frontiers in Cell and Developmental Biology, 2022)
During equine early gestation, trophectoderm forms chorion tissue, which is composed of two parts that one is covering allantoin, called allantochorion (AC) and another is covering yolk sac, which here we call vitelline-chorion (VC). Given that little is known about the equine trophoblast-derived chorion differentiation at an early stage, we first compared the transcriptome of AC and VC of day 30 equine conceptus based on RNA-sequencing. As a result, we found that compared to VC, there are 484 DEGs, including 305 up- and 179 down-regulated genes in AC. GO and KEGG analysis indicated that up-regulated genes in AC are mainly cell proliferation and cell adhesion-related genes, participating in allantois expansion and allantochorionic-placenta formation; dominant genes in VC are extracellular exosome and other cell adhesion-related genes implicated in direct and indirect conceptus-maternal communication. Additionally, as for the progenitor chorion tissue of equine chorionic gonadotropin secreting endometrium cup—the chorionic girdle (CG), which locates at the junction of the dilating AC and regressing VC, we revealed its unique gene expression pattern and the gene regulation during its further differentiation in vitro. Collectively, this study sheds light on the molecular events regarding the trophoblast differentiation and function at an early stage of the equine preimplantation conceptus.